Kedudukan Ahli Waris yang Berpindah Agama terhadap Harta Waris Menurut Hukum Waris Adat Bali - Dewa Ayu Herlina Dewi (Jurnal Preferensi Hukum, 2020)
A heir that change their religion from Hindu causing an heir to lose his inheritance rights. Because, in Bali's Customary Law of inheritance an heir has an obligation to heirs, families, and indigenous peoples. It is absolute for the heirs to get the right of inheritance. However, because of the affection of parents, many parents consider the position of heirs who convert by giving part of the inheritance that is not magical religious or a property that is not an inheritance but is said to be a grant. The purpose of this study is to determine the position or status of an heir who has converted and to know the possibility of whether the heirs can receive a gift outside of the estate. The method of research used normative juridical research methods, approaches made on the basis of major legal material by reviewing theories, concepts, legal principles and legislation related to this paper. Based on the contents of the study can be summarized as follows: 1. With the transfer of religion heirs, heirs can not carry out obligations as heirs to the heirs, families, and indigenous peoples. Thus the inheritance relationship between the heirs and the heirs is lost so that the legal consequences of the heir does not have the right to inherit. 2. Heirs can still accept the gift from their parents because of compassion. The gift may be a property which is not religiously magical and can also be given in the form of a grant.